INTEGRATING TECHNOLOGY IN BASIC ENGLISH CLASS - Mita Nur Aflah (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to determine the extent to which technology can be applied in the process of teaching and learning Basic English and affect student performance. Data obtained from classroom observations and interviews. The analysis shows how the application of technology provides an improvement in the teaching and learning process. The application of technology particularly computer games give students the opportunity to practice using English, as well as increasing students' interest in participating in classroom activities. In the process of applying this technology the development of the ability of students' vocabulary mastery can be seen. In short, this study shows that the application of technology raises a positive impact on students in the learning process in the classroom.